Revitalisasi Peran Bawaslu Sebagai Lembaga Quasi-Judicial Dalam Menyelesaikan Pelanggaran Administrasi Pemilu - Dimas Yoga Adhi Prabawa; Tri Susilowati (Universitas Sains dan Teknologi Komputer, 2023)
Elections are a means of popular sovereignty to elect members of the People's Representative Council, members of the Regional Representative Council, the President and Vice President, and to elect members of the Regional People's Representative Council, which are carried out directly, publicly, freely, secretly, honestly and fairly in the Unitary Republic of Indonesia. Indonesia is based on Pancasila and the 1945 Constitution of the Republic of Indonesia. As an electoral contestation, elections certainly have various kinds of potential violations in their implementation. One of the violations that has the greatest potential to occur is administrative violations. This article aims to analyze the revitalization of BAWASLU's role as a quasi-judicial institution in resolving election administration violations. The method used is descriptive analysis method. This article shows that Bawaslu is a quasi-judicial institution in elections which has the authority to handle election violations after determining the national election results. The authority to handle election violations after the determination of election results nationally, in this case is limited to administrative election violations. The authority to handle election violations after the determination of election results nationally, in this case is limited to administrative election violations. The authority of Bawaslu, of course, cannot be ignored. Moreover, currently Indonesia is starting to implement simultaneous elections. The implementation of the election mechanism simultaneously and in a short time will of course have implications for the process that occurs in the election.